Insights Into the Low Rate of In-Pump Thrombosis With the HeartMate 3: Does the Artificial Pulse Improve Washout? - Fang, Peng; Du, Jianjun; Boraschi, Andrea; Bozzi, Silvia; Redaelli, Alberto; Schmid Daners, Marianne; Kurtcuoglu, Vartan; Consolo, Filippo; de Zélicourt, Diane (Frontiers in Cardiovascular Medicine, 2022)
While earlier studies reported no relevant effect of the HeartMate 3 (HM3) artificial pulse (AP) on bulk pump washout, its effect on regions with prolonged residence times remains unexplored. Using numerical simulations, we compared pump washout in the HM3 with and without AP with a focus on the clearance of the last 5% of the pump volume. Results were examined in terms of flush-volume (Vf, number of times the pump was flushed with new blood) to probe the effect of the AP independent of changing flow rate. Irrespective of the flow condition, the HM3 washout scaled linearly with flush volume up to 70% washout and slowed down for the last 30%. Flush volumes needed to washout 95% of the pump were comparable with and without the AP (1.3–1.4 Vf), while 99% washout required 2.1–2.2 Vf with the AP vs. 2.5 Vf without the AP. The AP enhanced washout of the bend relief and near-wall regions. It also transiently shifted or eliminated stagnation regions and led to rapid wall shear stress fluctuations below the rotor and in the secondary flow path. Our results suggest potential benefits of the AP for clearance of fluid regions that might elicit in-pump thrombosis and provide possible mechanistic rationale behind clinical data showing very low rate of in-pump thrombosis with the HM3. Further optimization of the AP sequence is warranted to balance washout efficacy while limiting blood damage.